GENDER PARITY: GAPS AND ACHIEVEMENTS (Psychology Travelogs, 2025)
In our scientific work, we have highlighted a critical issue that has been kept silent for many years or has been exclusively declarative. We have outlined the genesis of gender parity in the world and Ukraine, and highlighted the psychological portrait of women by analyzing the classic works of Ukrainian literature. It is noted that the problem is not new, as it has been considered in the works of a considerable number of scientists and artists of the past and present, but social transformations bring new challenges.Scientific research aimed to identify achievements and gaps in gender parity in socially important areas of life to optimize social reforms and protect women.The article describes the history of the gender issue and the determinants of scientific research in this area. The vector of activity of the first domestic women's organizations is highlighted, which served as a fundamental basis for the further implementation of gender policy in Ukraine.We analyzed the regulatory framework for gender equality with its achievements and gaps (the declarative nature of many legislative acts). We demonstrated the dynamics of gender balance in state and political institutions.The work mentions the UN founding document, the UN Convention on the Elimination of All Forms of Discrimination against Women, the Beijing Declaration, which states the importance of women's access to all spheres of life and the country's resources. It emphasizes the need to improve the social status of women. Statistics on female military personnel in the Armed Forces of Ukraine are provided, and a comparative analysis of their current situation compared to the past is conducted.The systematic information and educational work on sex education and gender education was noted. Recommendations were provided for optimizing gender policy, citing as an example the systematic and fundamental work of specialists from Khmelnytskyi National University.
Keywords: genesis of the gender issue; socio-psychological determinants of gender policy formation; international standards on gender parity; positive and negative aspects of gender parity; optimization of gender policy